Garlic supplement lowers blood pressure in 40-60 years old hypertensive individuals, regulates oxidative stress, plasma cholesterol and protrombin index - Kravchuk, Olexandr M; Goshovska, Yulia V; Korkach, Yulia P; Sagach, Vadym F (Journal of Cardiovascular Medicine and Cardiology, 2021)
Background: Arterial hypertension is associated with tissue remodeling, oxidative stress and decreased production of such vasorelaxants as nitric oxide (NO) and hydrogen sulfide (H2S). Garlic shows promises in treatment of hypertension and could be used as an antioxidative agent and a source/precursor of H2S for decreasing of blood vessel stiffness. Methods: The study was carried out in Kozyatyn Central District Hospital (Kozyatyn, Vinnytsia region, Ukraine). Patients with grade II hypertension (40-60 years old men) and healthy individuals of the same age and gender were included into study (n = 10 in each group). Garlic supplement (400mg per day) was included to the treatment after 10 day of standard antihypertensive therapy (angiotensin converting enzyme inhibitors, beta blockers). Echocardiography, biochemical control of blood, determination of plasma H2S level and markers of oxidative-nitrozative stress were performed during study period. Results: It was found that 30 days of garlic supplement on the background of a standard antihypertensive therapy reduced both systolic and diastolic blood pressure by 16.5 and 12.5 mmHg respectively (P<0,01 for both). The plasma H2S level was significantly increased after 30 days of treatment. There was a positive effect of garlic supplement consumption on blood vessels in the form of a decrease in total peripheral vascular resistance by 10% (P<0,01). The production of reactive oxygen species and malonic dialdehyde was significantly reduced in blood plasma indicating antioxidative effect of garlic. Importantly, activity of constitutive NO synthase was restored and inducible NO synthase activity was inhibited. There was a decrease in plasma cholesterol by 30% and prothrombin index (P<0,001 for both). No significant changes in urea, creatinine, glucose, and erythrocyte counts were observed. Conclusion: The results of our study indicate the effectiveness of garlic supplement consumption as a hypotensive, cholesterol-lowering and mild antithrombotic agent in the treatment of hypertension in elderly patients. Garlic supplement consumption likely improves H2S and NO synthesis in hypertensive patients.